New species, new records, and taxonomical notes in Cerambycidae (Coleoptera) from the state of Espírito Santo (Brazil) - Santos-Silva, Antonio; Botero, Juan Pablo; Nascimento, Francisco Eriberto de Lima; Martins, David dos Santos (Papéis Avulsos de Zoologia, 2020)
Twenty three new state records of Cerambycidae are provided for Espírito Santo State, Brazil. Forgotten geographical records for Desmiphora (Desmiphora) cirrosa Erichson, 1847, and Cipriscola fasciata (Thomson, 1860) are mentioned. Notes on Metacriodion capixaba Fragoso, 1970, Potiaete maculata Martins & Galileo, 1999, and Eriphus mexicanus Audinet-Serville, 1834 are presented. The female of Trestonia grisea Martins & Galileo, 1990 is described for the first time. Stenoeme annularis Martins, 1980 is redescribed and a key to species of Stenoeme is provided. Four new species are described from the Brazilian state of Espírito Santo: Microibidion fiuzai, Iquiracetima venturai, Adesmus culiki, and Xenofrea simplicioi.